Rare case report of oral myiasis in immunocompetent patient - Aryan, Shubham; Sharma, Chavi; Kumar, Naveen; Garg, Ravinder; Khutan, Himanshu; Chahal, Jasmeen (Indian Journal of Case Reports, 2024)
Oral myiasis is a condition in which the soft tissues of different parts of the oral cavity are invaded by the parasitic larvae of flies known as maggots. Parasites causing myiasis belong to the order Diptera. Oral myiasis is often seen secondary to oral wounds, suppurative lesions, and extraction wounds, especially in individuals with neurological deficits. In such cases, neglected oral hygiene and halitosis attract the flies to lay eggs in oral wounds, resulting in oral myiasis. Hereby, we present the case of oral myiasis in a 45‑year‑old male patient who is immunocompetent and has a history of dental extraction.